SUBTITLING STRATEGY IN CLASH-A-RAMA ANIMATION SERIES SEASON 1 EPISODE 6: A KNIGHT TO REMEMBER - Wulan Sari, Dewi (Jurnal Sosial Humaniora dan Pendidikan, 2023)
Subtitling is the process of providing the equal meaning of what being said in the movie through the text written below the screen. The text written in the screen is known as subtitle. This research aims to find out the types of subtitling strategy in Clash-A-Rama Animation Series Season 1 Episode 6: A Knight to Remember.  Clash-A-Rama Animation Series Season 1 Episode 6: A Knight To Remember  is used as the source of the data. The data are every utterance in Clash-A-Rama Animation Series Season 1 Episode 6: A Knight to Remember. Qualitative method is applied in this research. This research used Gottlieb’s theory. 6 types of subtitling strategies are found in this research. They are transfer (63 data), paraphrase (62 data), deletion (9 data), imitation (7 data), condensation (2 data), and dislocation (1 datum)